Mixotrophic Cultivation of Microalgae in Cassava Processing Wastewater for Simultaneous Treatment and Production of Lipid-Rich Biomass - Vanessa Ghiggi Sorgatto; Carlos Ricardo Soccol; Denisse Tatiana Molina-Aulestia; Marco Aurélio de Carvalho; Gilberto Vinícius de Melo Pereira; Júlio Cesar de Carvalho (Fuels, 2021)
Cassava processing wastewater (CPW) is a highly polluting, liquid residue of cassava processing, usually discarded or treated anaerobically. However, it can serve as a low-cost culture medium for microalgae. After a preliminary evaluation of the growth of 10 microalgal strains in diluted CPW, the microalgae Haematococcus pluvialis SAG 34−1b and Neochloris (Ettlia) oleoabundans UTEX 1185 were selected for cultivation in CPW without a supply of additional nutrients and evaluated for their growth, lipid production, and nutrients removal. Maximal biomass concentrations of 1.79 g·L−1 for H. pluvialis and 3.18 g·L−1 for N. oleoabundans were achieved with 25% CPW medium on the 13th day of growth. The algae H. pluvialis and N. oleoabundans removed 60.80 and 69.16% of the chemical oxygen demand, 51.06 and 58.19% of total nitrate, and 54.68 and 69.84% of phosphate, respectively. On average, lipid productivities reached 0.018 and 0.041 g·L−1 day−1 for H. pluvialis and N. oleoabundans, respectively. Therefore, cultivating these microalgae in diluted CPW is a promising treatment for cassava wastewater with simultaneous valuable biomass production.